The Church of Worship : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Art at Massey University, Wellington, New Zealand - Francey, Joanne (Massey University, 2016)
The Church of Worship is a cult-like religious hyperreality performance and net-based project that explores and negotiates the parallels between religious devotion and celebrity adoration demanded by popular culture. This thesis uses the postmodern semiotic concept of hyperreality through Jean Baudrillard’s simulation and simulacra, as it’s theoretical framework. The project also explores Persona as a method for exploring the parallels between celebrity and religious icons or the concept of the ‘Hero’. The outputs of the church of worship include; a digital space of worship, performances, literature, and a series of overly refined fine art photographs. This project uses humour, abjection, and consumer and pop-cultural critique as central modalities.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Art